Statistical model for estimating losses due to foot-and-mouth disease in India - SINGH, RAJENDRA; TIWARI, C B; KUMAR, DINESH (The Indian Journal of Animal Sciences, 2013)
A stochastic model has been developed by incorporating a cost-benefit analysis system to study the merits and demerits of various strategies used to prevent, control or eradicate a disease in its operation area. This model will help in estimating the economic losses caused by morbidity and mortality and gain derived due to introduction of vaccination programme as a main strategy to control the disease. The stochastic model developed in the present study is TÂ R = E (P u rd + P12 r12) - v t=1 Application of the model has been demonstrated by using data collected from FMD outbreak at the IVRI. Izatnagar cattle farm. The overall expected economic losses due to morbidity and mortality were Rs 15.44 and Rs 4.58. respectively. which were 3.16 and 0.94%, respectively, of the average price value of animals. The overall total expected economic loss due. to morbidity and mortality combined was Rs 20.02 amounting to 4.10% of the average price value of the animals in the farm. Though presently the total cost of vaccination/animal-dose is Rs 4.00 including Rs 3.50 for the price ofa dose of vat cine. even then vaccination strategy for controlling the FMD’ in this country is a profitable proposition in endemic areas.